2. POLA INTERAKSI DAN PARTISIPASI MASYARAKAT DALAM PEMILIHAN GUBERNUR JAWA TENGAH 2013 - Budi Setiyono (Program Studi Sarjana (S1) Ilmu Pemerintahan, FISIP, Universitas Diponegoro, 2015)
People’s participation in the democracy process is one of important factors that marked democracy. Central Java 2013 Governor’s Election is the second governor election in Central Java. The shape of public participation and interaction patterns in 2013 Central Java Governor Election is the main question in this research. This research used survey method. The results showed in terms of political participation, the majority of voters in Central Java is those who were not engaged to any political party. There is no definite relationship between people’s choice in political party in 2009 legislative election and in governor’s election candidate. The majority of voters in Central Java in Pilgub were passive to political news through various media and campaigns.